Spectrophotometric and Conductometric Investigation of Azithromycin with Ca2+ Cation and Determination of Azithromycin in Dosage Form by Spectrophotometric Method - Sanavi Khoshnood, Razieh; Laal Zakaria, Toktam; Eshaghi, Zarrin (Asian Journal of Chemistry, 2012)
The interaction of the azithromycin with Ca(NO3)2.4H2O in methanol has been investigated by conductometric method to determine the number of complexes formed. The conductance data show that the stoichiometry of complex between azithromycin and Ca2+ is 2:1 [M:L2] in pure MeOH. The interaction of the azithromycin with Ca2+ was studied by spectrophotometric method under equilibrium conditions. Calcium is a biometal in human body. The interaction of azithromycin with Ca2+ salt has been found to form one complex with metal to ligand composition of 1:2. The value of (Kf = 3.7 × 104 M-2) was calculated from the absorption spectra for Ca2+-azithromycin complex at room temperature. Spectrophotometric method was developed and used to determine azithromycin-calcium at a lmax of 260 nm. The influence of pH, time, temperature and interferences has been tested. Also, the calibration graph of complex at the presence of HCl was linear (R2 = 0.980) over the range of (10-4-10-2 M). This simple method has been applied to the determination of azithromycin in dosage form.